Induced resistance for yellow rust and leaf blight in barley (Hordeum vulgare L.) using chemical mutagen - Sharma, Achla; Singh, Sarvjeet; Joshi, Neha; Meeta, Madhu; Sharma, Indu (Journal of Cereal Research, 2011)
Seeds of two commercial malt barley cultivars, VJM201 and DWR28, were treated with different concentrations of the chemical mutagen, 1, 3-buta diene diopoxide (DEB) to induce mutations for disease resistance. The number of chlorophyll/morphological mutants and mutation frequency, calculated 1000-1 M2 plants, was higher in DWR28 compared to VJM201 in M2. Many mutants were isolated with higher degree of resistance to yellow rust, brown rust and leaf blight, whereas some others showed higher degree of susceptibility to these diseases compared to the parent cultivars. Besides the mutants for disease resistance, some morphological mutants were also discovered especially for the quantitative traits like tiller number, spike length, etc. Plants having multiple mutant traits were also observed in both parent cultivars. Practical utility of desirable mutants having resistance to leaf rust, stripe rust and leaf blight has been discussed.